Apixaban Discontinuation for Invasive Or major Surgical procedures (ADIOS): A prospective cohort study. (June 2022) - Merli, Geno J; Kraft, Walter K; Eraso, Luis H; Galanis, Taki; Thomson, Lynda J; Ouma, Geoffrey O; Viscusi, Eugene; Gong, Jerald Z; Lam, Edwin
Background: Apixaban pharmacokinetic properties and some clinical reports suggest cessation 48 hours prior to surgery is safe, but this has not been demonstrated in a naturalistic setting. We sought to measure the residual apixaban exposure in patients who had apixaban held as part of standard of care perioperative management.Methods: This was a prospective, observational study of patients in whom apixaban plasma concentration and anti-Xa activity were measured while at steady state apixaban dosing and again immediately prior to surgery. Clinical management of cessation and resumption of apixaban was at the discretion of the treating physician.Results: Paired blood samples were provided by 111 patients. Ninety-four percent (104/111) of patients had measured apixaban concentrations of ⩽ 30 ng/mL. Only one patient had a value > 50 ng/mL. The median time between the self-reported last dose and presurgery blood sampling was 76 hours (range 32–158) for those who achieved concentrations ⩽ 30 ng/mL and 59 hours (range 49–86) for those > 30 ng/mL. Measured anti-Xa activity correlated well with apixaban exposure. Clinically significant nonmajor bleeding was reported in one patient at 1 week postsurgery. There was one venous thromboembolic event and one stroke in the perioperative period.Conclusion: In a naturalistic setting with a heterogeneous patient population, apixaban discontinuation for at least 48 hours before a procedure resulted in a clinically insignificant degree of anticoagulation prior to a surgical procedure.ClinicalTrials.gov Identifier: NCT02935751